2017
DOI: 10.1098/rsta.2016.0016
|View full text |Cite
|
Sign up to set email alerts
|

From slow to fast faulting: recent challenges in earthquake fault mechanics

Abstract: Faults—thin zones of highly localized shear deformation in the Earth—accommodate strain on a momentous range of dimensions (millimetres to hundreds of kilometres for major plate boundaries) and of time intervals (from fractions of seconds during earthquake slip, to years of slow, aseismic slip and millions of years of intermittent activity). Traditionally, brittle faults have been distinguished from shear zones which deform by crystal plasticity (e.g. mylonites). However such brittle/plastic distinction become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 98 publications
0
15
0
Order By: Relevance
“…This movement, that is, the very faulting, takes place either as creep: stable, slow sliding, or in the form of a series of earthquakes: unstable, fast slip intertwined with long periods of no motion. Faults thus accommodate strain on a momentous range of dimensions: on a spatial scale, from millimeters to hundreds of kilometers (for major plate boundaries), while also the time intervals range widely from seconds to minutes of earthquake slip, to years of slow, aseismic slip, and to millions of years of intermittent activity (e.g., Nielsen, 2017; Sibson, 2003). The textures and structures that develop in fault rocks depend on the amount and rate of shearing, and the physical conditions, that is, temperature and pressure, under which the shearing occurred.…”
Section: Formation Of Fault Rocks and Processes During Faultingmentioning
confidence: 99%
“…This movement, that is, the very faulting, takes place either as creep: stable, slow sliding, or in the form of a series of earthquakes: unstable, fast slip intertwined with long periods of no motion. Faults thus accommodate strain on a momentous range of dimensions: on a spatial scale, from millimeters to hundreds of kilometers (for major plate boundaries), while also the time intervals range widely from seconds to minutes of earthquake slip, to years of slow, aseismic slip, and to millions of years of intermittent activity (e.g., Nielsen, 2017; Sibson, 2003). The textures and structures that develop in fault rocks depend on the amount and rate of shearing, and the physical conditions, that is, temperature and pressure, under which the shearing occurred.…”
Section: Formation Of Fault Rocks and Processes During Faultingmentioning
confidence: 99%
“…Multiple scales, multi-physics interactions and nonlinearities govern earthquake source processes, rendering the understanding of how faults slip a grand challenge of seismology [ 1 , 2 ]. Over the last decades, earthquake rupture dynamics have been commonly modelled as a sudden displacement discontinuity across a simplified (potentially heterogeneous) surface of zero thickness in the framework of elastodynamics [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…[13]. Detailed geological and experimental study of fracture processes in rock massifs has shown that the fundamental tribological patterns of creep or stick-slip sliding can be successfully used to determine the causes and mechanisms of strong earthquakes in fault segments [14,15].…”
Section: Methodological Basismentioning
confidence: 99%